2017
DOI: 10.1590/1518-8345.1841.2908
|View full text |Cite
|
Sign up to set email alerts
|

Procedures for measuring and verifying gastric tube placement in newborns: an integrative review

Abstract: Objective:to investigate evidence in the literature on procedures for measuring gastric tube insertion in newborns and verifying its placement, using alternative procedures to radiological examination. Method:an integrative review of the literature carried out in the Cochrane, LILACS, CINAHL, EMBASE, MEDLINE and Scopus databases using the descriptors “Intubation, gastrointestinal” and “newborns” in original articles. Results:seventeen publications were included and categorized as “measuring method” or “techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 35 publications
(83 reference statements)
0
15
0
14
Order By: Relevance
“…Although the NEX technique has been used for years in pediatrics, this method has not been validated in the literature and studies have shown that tubes inserted with use of this technique are mostly misplaced, located above the gastroesophageal junction. (3) The most recommended indication for measuring the enteral tube is the nose -ear -half the distance between the xiphoid appendix and the umbilicus (NEMU) technique, (11,(12)(13)(14) as it allows the tube location inside the body of the stomach. Such a recommendation is supported by the American Academy of Pediatrics Neonatal Resuscitation Program and the National Association of Neonatal Nurses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the NEX technique has been used for years in pediatrics, this method has not been validated in the literature and studies have shown that tubes inserted with use of this technique are mostly misplaced, located above the gastroesophageal junction. (3) The most recommended indication for measuring the enteral tube is the nose -ear -half the distance between the xiphoid appendix and the umbilicus (NEMU) technique, (11,(12)(13)(14) as it allows the tube location inside the body of the stomach. Such a recommendation is supported by the American Academy of Pediatrics Neonatal Resuscitation Program and the National Association of Neonatal Nurses.…”
Section: Discussionmentioning
confidence: 99%
“…(1) The use of enteral tubes is one of the most common nursing procedures in the Neonatal Intensive Care Unit (NICU) and usually indicated for gastric decompression, enteral nutrition and medication administration. (2,3) In the neonatal population, enteral tube placement techniques are not well standardized and errors in correct positioning often occur. (4) In care practice, enteral tube placement techniques use several measurements to estimate the length of the tube to be introduced into the newborn (NB), namely the measurement from the tip of the nose to the ear lobe and until the xiphoid (NEX); from the tip of the nose to the ear lobe and from this point to the midline between the xiphoid and the umbilicus (NEMU); and from the tip of the nose to the ear lobe and from this to the umbilicus (NEU).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dentre as iatrogenias relacionadas ao uso de sondas de alimentação, destaca-se a localização inadequada 11,18 . Diversos são os métodos que a enfermagem utiliza para se certificar sobre a locação correta da sonda alimentadora, inclusive alguns não recomendados na atualidade por não atenderem a padrões de segurança do paciente 19 .…”
Section: Questões At/ap At/ep Et/ap Et/ep Punclassified